Analysis of The Influence of Exports, Imports, and The Amount Of Currency in Circulation on Inflation in Indonesia from 1991 to 2022 Using Error Correction Model (ECM) - Iwan Harsono; Bunga Fajriati; Dodo Kurniawan; Syahru Ramadhan; Muhajirin Muhajirin (Yayasan Riset dan Pengembangan Intelektual, 2024)
High inflation can have a negative impact on the economy. Based on the economic conditions in Indonesia, the rate of inflation experiences fluctuations each year due to various factors. This research aims to analyze the influence of exports, imports, and the amount of currency in circulation on inflation in Indonesia. It is a quantitative study utilizing time series data from 1991 to 2022. Data analysis is conducted using the Error Correction Model (ECM) to examine the long-term and short-term effects of the observed variables. The results indicate that exports have a positive and significant impact on inflation in the long term but not significantly in the short term. On the other hand, imports and the amount of currency in circulation have a significant influence on the inflation rate in Indonesia, both in the long and short terms. Simultaneously, exports, imports, and the amount of currency in circulation significantly affect the inflation rate in Indonesia, both in the short and long terms.